Meta-Analysis for Public Management and Policy. - Ringquist, Evan (Wiley, 2013)
Meta-Analysis for Public Management and Policy is a groundbreaking book that includes a proven set of tools for making sense of mountains of sometimes inconsistent conclusions from original research. The tools of meta-analysis can help to improve scholarship, ensure more accurate tests of theories, provide clearer and more authoritative advice for policy and management, and ultimately contribute to the wider knowledge base of public management and policy and the social sciences more broadly. This important resource contains an in-depth explanation of the six-stage process for c.